Efficacy and neural mechanism of acupuncture for essential hypertension: Study protocol for a randomized clinical trial - Xiao-Ya Wei; Xin-Yuan Jiang; Lu Wang; Chao-Qun Yan; Na-Na Yang; Ze-Yi Wang; Xiao Wang; Hang Zhou; Chih-Kai Lee; Cun-Zhi Liu; Xu Wang; Jian-Feng Tu (PLoS ONE, 2025)
Background Hypertension is a major risk factor for cardiovascular diseases. Acupuncture has been used to control blood pressure in clinical, however, the high-quality clinical evidence is insufficient and the underlying mechanisms remain unclear. Objectives This study aims to evaluate the efficacy of electroacupuncture for patients with essential hypertension (EH) compared with sham electroacupuncture and explore the neural mechanism. Study design and methods his is an 8-week, parallel-grouped, randomized clinical trial. A total of 66 patients diagnosed with EH are randomly assigned (1:1) to receive either the electroacupuncture or sham electroacupuncture treatment 3 sessions per week for 4 weeks. The primary outcome is the mean systolic blood pressure change at week 4 from the baseline measurement. The independent sample t-test will be used to compare the differences between two groups. The secondary outcomes include the change in mean diastolic blood pressure, the proportion of patients with controlled blood pressure (< 140/90 mm Hg), and quality of life. The outcome variables are measured at baseline, week 2, week 4 and week 8. Functional magnetic resonance imaging scans, pulse rate variability acquisition, and image-based photoplethysmography recording are performed at baseline and the end of the intervention period to explore acupuncture-related neuroplasticity changes. Correlation analyses are performed to investigate the relationships between the neural changes and clinical symptoms. Adverse events during the trial are monitored. Trial registration Chinese Clinical Trials Registry, the number is: ChiCTR2400082315 (https://www.chictr.org.cn/showproj.html?proj=223840).